South Africa - Report on Observance of Standards and Codes : Banking Supervision, Insurance Supervision, and Securities Regulation - World Bank; International Monetary Fund (Washington, DC, 2013)
This assessment found South Africa s regulatory system to be fundamentally sound and compliant with international standards. Banking supervision has been effective and has helped limit the impact on the financial sector of the global financial crisis. The assessment recommended that the bank registrar s remedial powers for addressing problems in banks should be strengthened and that a specific regulation for dealing with country and transfer risk be introduced.The FSB is also undertaking a study of the OTC market. Limited progress has been made by the Department of Trade and Industry (DTI) to implement significant amendments to the Companies Act that were enacted in 2007 and in 2009. If progress continues to lag, consideration should be given to reassigning responsibility for these functions to the Financial Services Board (FSB).